EXPERIMENTAL STUDY ON THE FAILURE PATTERN OF COHESIVE SOIL UNDER FINNED SLABS THROUGH LOAD TESTING - Megasim; M. Yusuf; Vivi Bachtiar (Jurnal Ilmiah Teknik Sipil, 2025)
Rapid infrastructure development demands reliable road pavement systems, especially on expansive and low-bearing capacity cohesive soils. This research investigates the addition of fins to pavement slabs as an innovative rigid pavement design. The study investigates how fins and their varying inclination angles 0°, 30°, 60°, 90° affect failure patterns and bearing capacity in cohesive soil. Tests on five slab types revealed distinct behaviors. Finless slabs and those with 90° fins showed shallow local shear failure. The 0° finned slab formed wedge failure due to stress concentration. Slabs with 30° and 60° fin inclinations exhibited a more distributed failure pattern with a wider plastic zone, indicating efficient stress distribution. The highest ultimate bearing capacity was achieved by 60° finned slab, reaching 10.60 kN, followed by the 30° finned slab at 6.20 kN. The 0° finned slab showed the bearing capacity at 3.53 kN. These significantly outperformed the finless slab at 3.40 kN and the 90° finned slab at 4.00 kN. These findings suggest that specific fin configurations can significantly improve slab performance on cohesive soil, offering a solution for problematic soil conditions in rigid pavement systems.